Tradisi Komunikasi Kiai Pesantren Annuqayah Guluk-Guluk Sumenep Jawa Timur - Fathorrahman, Fathorrahman; Siregar, Fauzan Ahmad; Muadin, Akhmad (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
Kiai communication is a unique pesantren treasure, full of characteristics and attractiveness. The communication treasures of kiai eventually become the tradition of the pesantren which is always interesting to be discussed. Regarding the tradition of kiai communication at Pesantren Annuqayah Guluk-Guluk, a qualitative approach was conducted by collecting data in the form of words holistically using interviews, observation, and document studies. The data were analyzed using the following steps: data condensation, data display, and drawing conclusions or verification. This research has succeeded in revealing the fact that the communication tradition of kiai is generally categorized into two parts: 1) outward communication (bil lisān and bil āl), and 2) inner communication. The communication of kiai at pesantren Annuqayah refers to the following principles; qaulan balīgan, qaulan maisran, qaulan ma'rfan, qaulan karīman, qaulan sadīdan, and qaulan layyinan.